Adult Attachment Style, Emotion Regulation, and Social Networking Sites Addiction - Liu, Chang; Ma, Jian-Ling (Frontiers in Psychology, 2019)
While there is substantial evidence that emotion regulation plays a role in the maintenance of substance and behavior addiction, its role in addiction to social networking sites (SNS) remains unclear. Drawing on attachment theory, we explore whether emotion regulation mediates the relationship between insecure attachment and SNS addiction among 463 college students. The participants completed the short version of the Experience in Close Relationships Scale, Difficulties in Emotion Regulation Scale, and Chinese Social Media Addiction Scale. The results indicated that attachment anxiety positively predicted SNS addiction and emotion regulation mediated this link. These findings suggest that individuals’ affective regulation capability should be a target of future interventions and treatments.